Fruit and vegetable intake of youth in low-income communities - Sempa, Judith (Kansas State University, 2016)
The objectives of the study were to assess fruit and vegetable intake of 6th to 8th grade youth in low-income areas, assess their food environment, and determine factors that influenced fruit and vegetable consumption. Sixth to eighth grade youth from two low-income communities in each of the three states of South Dakota, Kansas and Ohio were involved in the study. Fruit and vegetable intake was measured using the National Cancer Institute (NCI) fruit and vegetable screener tool. The food environment was measured using the Nutrition Environment Measures Survey for Restaurants (NEMS-R) and the Nutrition Environment Measures Survey for Stores (NEMS-S) tools. A generalized linear mixed model in PROC GLIMMIX was used to assess possible predictors of fruit and vegetable intake. Average daily fruit and vegetable consumption for males and females was 3.8 cups (95%CI= 2.4-6.0) and 3.1 cups (95%CI=2.0-4.9) respectively. Grade, gender, ethnicity, community, and state of residence did not influence fruit and vegetable consumption, while fruit and vegetable availability at home influenced intake. Youth had a favorable view of their food environment, contrary to the findings of objective measures.
Keywords: food environment; youth; low-income areasFruits and vegetables